Altitude: How does it affect performance? - Wilber, R.; Schnittger, J. (2001)
Participants at the Olympic Winter Games at Salt Lake City will compete at venues that are located at elevations ranging from 1,250 to 2,200 meters (4,100 to 7,216 feet). What effect will altitude have on the performance of Olympic athletes? Will some sports be affected by altitude more than others? How will altitude influence performance in sports that have an aerodynamic component? What is the optimal strategy for competing at altitude - long term preparations and other considerations? Please note: The figure skating venues - Salt Lake City Ice Center and Steiner Arena are at an elevation of 4,113 feet. The United States Olympic Committee (USOC) and the American College of Sports Medicine (ACSM) felt concerns about training and competing at altitude was so important that they made altitude the topic of their 5th Annual USOC and ACSM Human Performances Summit held in Baltimore, Md., June 3, 2001. The summit consisted of short presentations by a panel of coaches and researchers followed by a town meeting discussion with an audience of coaches, educators and scientists. This article is intended to provide a "snapshot" of key discussion from the summit. Note: This article is information only; it is not a policy statement of either the USOC or the ACSM. Specific physiological responses and limitations occur in athletes at altitude, including decrements in aerobic performance, maximal aerobic power (VO2max), and training intensity. Changes in resting and exercise heart rate may also occur. These physiological responses and limitations can significantly impair an athlete's ability to train and compete effectively at altitude. At the Human Performances Summit, different sports discussed their plans for training and competing at altitude prior to the Winter Olympic Games in Salt Lake City. Long track speed skating moved their coaches and athletes to Park City, Utah, where they plan to stay and train until the Games in February of 2002. Mike Crowe, national sprint coach said, "Our coaches and athletes want to know everything possible about training and competing at altitude because speeds are higher at altitude and technique changes such as the lean in the turn, etc." The long track speed skaters will use supplemental oxygen during workouts, which will allow them to use low altitude training (see Q and A section of this article for explanation of high - low training). They will "live high" at Park City (elevation 6,570 ft.) for the purpose of increasing the amount of red blood cells and hemoglobin. The supplemental oxygen will allow them to train in a simulated seal level environment. In addition, the long track speed skaters will have the advantage of training nearly every day on the Utah Olympic Oval, where they will become familiar with all the subtleties of the ice surface, which should provide them with a competitive edge during the Olympic winter Games. "Figure skating is in the process of educating their coaches on the importance of training at altitude," said Shelly Provost-Craig. Four options are suggested for coaches and athletes to plan for altitude training prior to the Olympic Winter Games. A. Attend a pre-Olympic camp for 14 to 18 days immediately prior to the Olympic Winter Games, spending seven to 10 days in Colorado Springs (6,035 feet) and the remaining time in Salt Lake City (1,100 feet). B. "Live high - train low" using the Colorado Altitude Training (CATTM) room at home, starting August 1, 2001, with a systematic progression in altitude. Blood chemistry will be checked and a baseline established in July 2001, deciding is iron supplementation is necessary. Evaluation of this option will be completed at Skate America at Colorado Springs in October 2001, and final modifications will be made in preparation for the Olympic Games in February 2002. C. Coaches and athletes may combine options A and B. D. Athletes currently living and training at altitude (Big Bear Lake, California 5,100 feet) may continue to live and train there. Ice Hockey national women's team coach, Ben Smith, stated, "Ice Hockey is different from other sports represented at the summit because team is a big factor compared to the individual program. The length of competition may be as long as a sprint or up to a full game (three hours, including a warm up process). Another factor is age variation, women ice hockey players range in age from 16 to 30 years-of-age. The team has been in Lake Placid, New York, since November 2000. After selecting the top 20 athletes, the team will begin a 35-game training schedule. Final team selection should be complete by Christmas, and that helps athletes mentally - knowing that they are on the team by the Christmas break. The team will most likely spend the month of January training in Colorado Springs (elevation 6,035 feet) and move to the Olympic Village (elevation 4,331 feet) on February 1 with the first game on February 8. The team's schedule for January and early February 2001 allows for acclimatization and training at altitude prior to competition. Nordic Combined (cross country skiing and ski jumping) lives and trains most of the year at Steamboat Springs, Colo. With and elevation of approximately 7,000 feet. Coach Tom Steitz told the audience, "Seventy-five percent of the team was born and raised at 2,000 meters which is a distinct advantage because they are immediate responders for training and competing at altitude." A responder is an athlete whose performance is not significantly impaired at altitude. According to Steitz, "A team member born and raised at sea level will take at least a year to become a responder, and he/she may take as long as three years before showing performance improvement." Steitz's team has used supplemental oxygen in a backpack unit format for the past two years. They use it during high intensity workouts in the early season, but they will not use it as they get closer to the Games, because they will be trying to duplicate the projected race pace of the Olympic competition without the aid of additional oxygen. The Nordic combined athletes live at the same altitude as the Olympic winter Games venue, but they feel like the Olympic venue site is 500 feet higher because the air is very dry. Athletes use humidifiers in their rooms to reduce the dryness of the air. Q AND A The remainder of the summit was conducted in a town meeting format with the audience asking questions of the panel members and contributing information. What is the live high - train low strategy? It proposes that athletes can improve sea level endurance performance by living high (2,000 - 2,700 meters/6,560 - 8,860 feet) and training simultaneously at a low elevation (1,000 meters/3,280 feet). It is believed that by living at a higher altitude, there will be an increase in athletes' serum erythropoietin (EPO), red blood cell mass and hemoglobin. Training at low altitude while living high allows athletes to work at an intensity similar to sea level. This "high-low" altitude training leads to the enhancement of sea level VO2MAX and endurance performance. What is a "nitrogen house"? It was originally developed by the Finns in the early 1990s for the purpose of stimulating an altitude environment. In Finland, there are nitrogen houses (also known as nitrogen apartments) that simulate an altitude environment equivalent to 2500 meters/8,200 feet. A ventilation system introduces a 100 percent nitrogen gas into the apartment, which has the effect of diluting the oxygen concentration thereby simulating an altitude environment. Athletes using the nitrogen apartment follow the "high - low" training strategy by living and sleeping in the nitrogen apartment for 12 to 18 hours a day, but they train at sea level. Data shows that use of a nitrogen apartment may produce beneficial changes in serum EPO and red blood cell mass, which may lead to improvements in endurance performance. Does training at altitude deplete iron supplies? Ferritin, the storage form of iron, should be adequate before an athlete attempts training at altitude, because data suggests that the synthesis of new red blood cells will not take place in endurance athletes that are iron deficient. Is dehydration more of a problem at altitude than at sea level? Yes, during the first few days of training at altitude, athletes have a tendency toward increased respiratory water loss due to more frequent and deeper breathing. They also tend to have a higher urinary water loss. Athletes need to maintain fluid balance not only during workouts but during the non-workout part of the day, as there is potential for performance limiting dehydration. Why do athletes at altitude need to be diligent about consuming carbohydrates? Recent studies suggest that carbohydrate utilization is enhanced and fat utilization is reduced at altitude. By using carbohydrate stores more rapidly at altitude, it is important that athletes make an effort to replenish those stores by eating and drinking foods and beverages high in carbohydrate. Is blood lactate a physiological limitation to altitude training? During the first few hours and days at altitude, blood lactate response during submaximal and maximal exercise may be more pronounced compared with similar exercise at sea level. Coaches and athletes need to be aware of this as they design individual workouts; high blood lactate levels and accompanying high concentrations of hydrogen ions (H+) may contribute to skeletal muscle fatigue. What effect does altitude have on hydrogen ion buffering? Hyperventilation is one of the first physiological responses at altitude, and it leads to an increase in respiratory removal of hydrogen ions and an increase n blood pH. The increased alkalinity in the respiratory system stimulates the kidneys to increase the rate of renal bicarbonate (HCO3-) excretion within hours after arriving at altitude. Since HCO3- is an important metabolic buffer of H+ produced during exercise, a loss of HCO3- may adversely affect maximal or supramaximal performance. Do athletes have sleep problems at altitude? They may experience some degree of sleep disturbance, particularly athletes training at altitude for the first time. The problem usually disappears after the athlete is acclimatized. Athletes will also need additional recovery time at altitude, both during workouts (longer rest intervals) and between workouts (an extra recovery day between hard workouts, afternoon naps, etc.) Will athletes frequently experience upper respiratory or gastrointestinal infection at altitude? Some athletes may be subject to these infections after arrival at altitude. It has been suggested that these infections may be due to an altitude-induced suppression of athletes' immune systems. Is there an increased instance of asthma among athletes at high altitude? Each athlete's asthma problems should be addressed individually. Recommendation is to take the athlete to altitude, identify the problem and work toward solutions. How long does it take for athletes to acclimatize? Acclimatization takes approximately three weeks; it will vary from athlete to athlete. Once acclimatized, athletes need to return to altitude every two to three weeks to maintain the effect. Why do athletes use supplemental oxygen? Supplemental oxygen is used to simulate sea level or hyperoxic (above-normal level of oxygen) conditions during high-intensity workouts at altitude. Using oxygen in this method is modification of the "live high - train low" strategy. Supplemental oxygen is used effectively at the U.S. Olympic Training Center in Colorado Springs, Colo., where athletes live at 1,885 meters/6,180 feet but can simulate sea level training with its use. Scientific data on the use of supplemental oxygen is limited, however it suggests that high-intensity workouts may enhance performance at moderate altitude. Are there other altitude simulation devices? Yes, here are names and descriptions of two such devices, both designed for "sleep high - train low." Is there a "rule of thumb" for the types of sport/exercise that benefits most from altitude training? In general, with acclimatization up to 10 days, athletes competing in events of less than two minutes, show minimal improvement in performance at altitude. For events lasting longer than two minutes, there appears to be a minimum of two percent improvement in endurance performance at altitude. This suggests that acclimatization lasting 10 days or longer may lead to improvements in endurance performance at altitude in events lasting two to 16 minutes. Conclusion The lively discussion on training and competing at altitude that took place at the USOC and ACSM Human Performance Summit is merely a brief look at the factors involved. Any coach or athlete interested in trying some of the strategies should consult with reputable sport scientists and other medical professional staff before undertaking an altitude program.